Football and marriage - and the UEFA draw - Wallace, M.; Haigh, J. (Significance, 2013)
The draw for the matches in this year`s UEFA Champions League produced a surprise: the draw result was exactly the same as at the rehearsal. Sixteen teams had been paired against each other in exactly the same way, twice running. Yet the draw was supposed to be random. Was it a 2 million to one coincidence? A fix? Or was it only to be expected?